ACE/ACTN3 GENETIC POLYMORPHISMS AND ATHLETIC PERFORMANCE OF FEMALE SOCCER PLAYERS` - Jeremic,Dejan (2019)
ABSTRACT Objective: Previous studies have shown controversial relationships between ACE and ACTN3 gene polymorphisms and sports performance. Thus, the aim of our study was to assess anaerobic and aerobic performance indicators of young female soccer players with different ACE/ACTN3 gene profiles. Methods: Twenty-seven female soccer players aged 16-18 underwent acceleration, speed, strength, anaerobic power and aerobic endurance tests and had their ACE and ACTN3 polymorphisms determined. Results: Based on genetic analysis, they were divided into the following groups: ACE II (n=2), ACE ID (n=11), ACE DD (n=14), ACTN3 XX (n=5), ACTN3 RR (n=7) and ACTN3 RX (n=15). ACE DD and ACE ID groups differed significantly in terms of results achieved on the 5 m sprint test (1.15±0.05 s vs 1.10±0.05 s, P=0.42). ACTN3 RR and RX achieved better results than the ACTN3 XX group in seven continuous vertical jumps (26.57±1.59 cm vs 25.77±2.51 cm vs 22.86±1.16 cm, respectively; P=0.007 for RR vs XX and P=0.021 for RX vs XX). Conclusion: High prevalence of ACE DD and ACTN3 RX genotypes in our subjects may suggest that faster and more powerful young females tend to perform better in soccer. Nevertheless, the absence of differences in most of the physical test results indicates that different genotypes are compatible with high-level soccer performance, meaning that it is the phenotype-genotype interaction that makes a successful female soccer player. Level of Evidence I, Prognostic studies — Investigating the effect of a patient characteristic on disease outcome.